Influence of Plant Population and Nitrogen-Fertilizer at Various Levels on Growth and Growth Efficiency of Maize - M. I. Tajul; M. M. Alam; S. M. M. Hossain; K. Naher; M. Y. Rafii; M. A. Latif (The Scientific World Journal)
Field experiments were conducted to evaluate plant population and N-fertilizer effects on yield and yield components of maize (Zea mays L.). Three levels of plant populations (53000, 66000, and 800000 plants ha−1 corresponding to spacings of 75 × 25, 60 × 25, and 50 × 25 cm) and 4 doses of N (100, 140, 180, and 220 kg ha−1) were the treatment variables. Results revealed that plant growth, light interception (LI), yield attributes, and grain yield varied significantly due to the variations in population density and N-rates. Crop growth rate (CGR) was the highest with the population of 80,000 ha−1 receiving 220 kg N ha−1, while relative growth rate (RGR) showed an opposite trend of CGR. Light absorption was maximum when most of densely populated plant received the highest amount of N (220 kg N ha−1). Response of soil-plant-analysis development (SPAD) value as well as N-content to N-rates was found significant. Plant height was the maximum at the lowest plant density with the highest amount of N. Plants that received 180 kg N ha−1 with 80,000 plants ha−1 had larger foliage, greater SPAD value, and higher amount of grains cob−1 that contributed to the maximum yield (5.03 t ha−1) and the maximum harvest index (HI) compared to the plants in other treatments.